Analysis of the conditions for the occurrence of the effect of a minimum of friction in hybrid bearings based on the load separation principle. (February 2019) - Polyakov, Roman; Savin, Leonid; Fetisov, Alex
Reliability of rotating machinery is determined to a considerable degree by the bearing units. For several applications the requirements in rotational speed, bearing load and maximal vibration level are so extreme that neither rolling-element bearings nor fluid-film bearings could provide necessary operating characteristics during all regimes of operation. Hybrid bearings, which are a combination of rolling-element and fluid-film bearings, can improve performance characteristics and reliability of the rotor-bearing systems. A hybrid bearing, where a rolling-element bearing and a fluid-film bearing are positioned parallel to the vector of external load (PLEX), has the following advantages compared to a single bearing, whether rolling-element or fluid-film one: increase of life expectancy, load capacity increase, friction reduction, thermal regime enhancement, increase of stiffness, and damping properties. The present paper presents the results of theoretical and numerical research of friction characteristics of PLEX in mixed sliding and rolling friction, i.e. combination of viscous and rolling contact friction, regime. The conditions of minimum friction effect occurrence have been substantiated, and rational relations between characteristics of hybrid rolling-element bearings and fluid-film bearings needed for provision of such effect have been experimentally proven. Finally, the paper presents recommendations regarding design of such hybrid bearings for heavily loaded bearing nodes of rolling mills.